The tech-savvy real estate agent - Gruman, Galen (Peachpit, 2006)
Sure, you know how to use the MLS database, but do you know how to effectively establish a Web presence or do customer outreach via email or the Web? There are all kinds of ways you can use technology to market your practice and service your clients, but if you're like most realtors you've probably only scratched the surface. In this easy-to-understand guide, author Galen Gruman draws on his more than 20 years of experience as a tech-industry author and journalist to show you how to become a better real estate agent by learning and effectively using current computer technology and tools in your business. You'll learn what technology to use as well as what technology not to use,so that you're certain to spend your tech dollars effectively. In major sections on marketing, communications, and transaction management, Galen covers everything from the elements of a good Web site to evaluating devices and services, working in multiple locations, creating transaction libraries, using digital photography, converting documents to electronic forms, and more. This book also includes a CD-ROM for both Windows and Mac with templates, product and technology links, tryout and free software tools, and even quizzes for use in classroom and training environments.